Application of a BIM model for demolition work planning - Radziejowska, Aleksandra; Szeląg, Jakub (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The article explores the use of BIM tools in the planning of demolition works for a structure. The analysis includes the utilization of BIM to create a three-dimensional model of the object, with a level of detail that allows for accurate cost estimation of the demolition. Additionally, it enables the precise determination of the demolition sequence, identification of potential issues, and optimization of the process. BIM tools also facilitate the analysis of the environmental impact of demolition and the safety of workers. Furthermore, through virtual simulation, demolition planning can take into account ecological and social effects. The authors highlight that the application of a BIM model simplifies risk analysis and allows for the creation of scenarios for the duration of demolition work, enabling the selection of the fastest solution while simultaneously reducing costs and optimizing resources. Conclusions drawn from the case study demonstrate how advanced BIM tools can revolutionize the planning of demolition processes, introducing a new level of precision and a sustainable approach to such projects.